2020
DOI: 10.21203/rs.3.rs-19653/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Obesity prevention in the early years: a mapping study of national policies in England from a behavioural science perspective

Abstract: Background Evidence indicates that early life is a critical time for determining future risk of obesity. A sharper policy focus on pregnancy and early childhood would be useful to improve obesity prevention efforts. This study aimed to systematically identify and categorise the policy levers being used in England that have potential to influence early lifecourse (pregnancy and 0-5 years) and identify how these policies interface with energy balance behaviours. The objective is to identify gaps and where furt… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
(24 reference statements)
0
1
0
Order By: Relevance
“…It is well known that theory-based behavioral models are crucial in adopting a new behavior [32][33][34]. We observed that 69.6%, 41.9%, and 12% of our study participants, respectively, had a high level of capability, opportunity, and motivation to receive the COVID-19 vaccine according to the COM-B model.…”
Section: Plos Onementioning
confidence: 61%
“…It is well known that theory-based behavioral models are crucial in adopting a new behavior [32][33][34]. We observed that 69.6%, 41.9%, and 12% of our study participants, respectively, had a high level of capability, opportunity, and motivation to receive the COVID-19 vaccine according to the COM-B model.…”
Section: Plos Onementioning
confidence: 61%